The Tokyo Trial war criminals and Japan's postwar international relations - Higurashi, Yoshinobu 1962-; Higurashi, Yoshinobu 1962- (2022)
The Tokyo Trial, like the Nuremberg Trial, was unique as a judicial event. Presided over by eleven Allied judges, Japan's wartime leaders were individually tried in an international court of justice for crimes against international law. After two years of hearings, a majority judgment found twenty-five of the accused guilty; seven were sentenced to death. However, factionalism amongst justices and competing political interests served to undermine the final judgment, widely criticized as 'victor's justice.' Some seventy years later, its legacy continues to inform international politics and polarize ideological debate."--Page 4 of cover.
Preface. -- Chapter 1. Viewpoints on the Tokyo Trial. 1. Controversy over enshrinement at Yasukuni 2. Distinguishing between "Class A" and "Class B and C" 3. "Civilization's justice" theory vs. "victor's justice" theory -- Chapter 2. How the framework of the Tokyo Trial was formed. 1. Lessons learned from the failure of the Treaty of Versailles 2. US initiative vs. cooperation among the Allies 3. The decision not to charge the emperor and the motives of concerned countries -- Chapter 3. What charges did the Allies bring?. 1. Launching the International Prosecution section 2. Identifying defendants and determining charges 3. Logic of the prosecution -- Chapter 4. How Japan responded. 1. Cooperation and resistance 2. Logic of the defense 3. Defense of state and defense of individuals -- Chapter 5. How the judgment was written. 1. Disruption of the bench 2. Reorganization of the judge group and the judgment 3. How to interpret Pal's judgment -- Chapter 6. Why a second Tokyo Trial was not held. 1. International trial and subsequent trial 2. MacArthur's persistence 3. Shift toward completion of the war crimes trial -- Chapter 7. How the release of war criminals commenced. 1. When and how 2. War criminal clause in the San Francisco Peace Treaty 3. "Serious domestic problems" after regaining independence -- Chapter 8. Why were Class A war criminals released? 1. Start of recommendations for clemency 2. Increased calls for the "radicalist approach to release" 3. What lies beyond the Tokyo Trial -- Afterword -- Chronological table -- List of references -- Index -- About the author.
Revised English edition of 2008 book, To?kyo? Saiban, winner in the History and Civilization category of the 30th Suntory Prize for Social Sciences and Humanities.
Includes bibliographical references (pages 359-373) and index.
Keywords: 1946-1948.; Tokyo Trial, Tokyo, Japan, 1946-1948.; War crime trials -- Japan -- Tokyo; Trial and arbitral proceedings; informational works